'Annoyed Every Inch of Their Passage': Admiral Lord Keith's counter-invasion campaign, May 1803–August 1805. Issue 2 (3rd April 2023) - Robson, Martin L.
Abstract : Defence against invasion is a prime Royal Navy task, but arguably the campaign of 1803 to 1805 has been overshadowed to the point of neglect. Here, Admiral Keith directed a detailed plan of defence which stretched from the harbour of Boulogne to the Thames estuary and encompassed craft from 74-gun ships of the line to oared boats owned and manned by civilian volunteers. This was supported by a network of communications that would give the government and army the earliest possible notice of impending attack and also facilitate an active naval defence that had been developed with advice from civilian pilots to allow craft defending effectively inshore to operate to best advantage. In essence Keith built a defence force from Havre to Texel that, although not called upon, provided an effective counter while supporting the battle squadrons blockading the main French fleets.